Community Fluoridation Status and Caries Experience in Children - James A. Gillcrist, DDS, MPH; David E. Brumley, DDS, MPH; Jennifer U. Blackford, PhD (Blackwell Synergy, 2001)
This study compares dental caries experience in fluoridated and nonfluoridated communities. Methods: A dental health survey designed to collect data on caries experience and treatment needs for community-specific public health planning purposes was conducted in public elementary schools during the 199fj-97 school year. Oral examinations of 17,256 children were completed, representing 93 percent of children residing in 62 East Tennessee communities.